Mental health recovery: a strengths-based approach to culturally relevant services for African Americans. - Jones LV; Hardiman ER; Carpenter J (Journal of Human Behavior in the Social Environment, 2007)
Strengths-based approaches that emphasize culturally competent services and naturally occurring community support may be more appropriate than traditional mental health services for African American adults with psychiatric disabilities. An examination of the literature on service utilization and treatment needs for this population highlights the paucity of empirical studies in these areas, while an exploration of the literature related to psychiatric recovery, a prominent strengths-based framework, reveals insufficient application of the approach to the specific interests of African American service recipients. We suggest that recovery is in fact highly compatible with such culturally relevant approaches as the Afrocentric model, and argue that the concept of recovery may therefore provide a resonant and particularly useful framework for practice with this population. Implications for research, practice and policy are discussed. doi:10.1300/J137v15n02_15